Dihydrazide compound, curable resin composition, sealant for liquid crystal display element, vertical conductive material, and liquid crystal display element

By using a specific structure of dilate compounds in the sealing agent of the LCD component as thermal curing agent, the problem of insufficient curing and liquid crystal pollution of the sealing agent is solved, and the effect of high stability and low pollution is achieved.

CN115515929BActive Publication Date: 2025-01-28SEKISUI CHEMICAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202180031495.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-06-04
Filing Date
2021-06-03
Publication Date
2025-01-28
Estimated Expiration
2041-06-03

AI Technical Summary

Technical Problem

In the narrow frame design, the light curing of the sealant is blocked by the black matrix, resulting in insufficient curing and easy to cause liquid crystal contamination. At the same time, when using a thermal curing agent to improve curability, it is difficult to take into account both the storage stability and the contamination of liquid crystals.

Method used

The dilate -sulfid compounds with a specific structure are used as thermal curing agent, which improves the preservation stability, curing and adhesion of the sealing agent through its application in the cured resin composition, and reduce liquid crystal pollution.

Benefits of technology

The efficient curing and low liquid crystal pollution of the sealing agent is achieved, and the high -quality and stability of the liquid crystal display component is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
  • Figure BDA0003907709120000031
    Figure BDA0003907709120000031
Patent Text Reader

Abstract

The object of the present invention is to provide a novel dihydrazide compound. In addition, the object of the present invention is to provide a curable resin composition containing the dihydrazide compound and having excellent storage stability, curability and adhesion, and a sealant for liquid crystal display elements, a vertical conductive material and a liquid crystal display element formed by using the curable resin composition and having excellent low liquid crystal contamination. The present invention is a dihydrazide compound having a divalent aliphatic hydrocarbon group in which one or more hydrogen atoms are substituted by a group containing an aromatic ring.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a novel dihydrazide compound. In addition, the present invention relates to a curable resin composition containing the dihydrazide compound and having excellent storage stability, curability and adhesion, and a sealant for a liquid crystal display element, a vertical conductive material and a liquid crystal display element formed by using the curable resin composition and having excellent low liquid crystal contamination. Background Art

[0002] In recent years, as a manufacturing method for liquid crystal display elements such as liquid crystal display units, from the viewpoint of shortening the production cycle time and optimizing the amount of liquid crystal used, a liquid crystal dropping method called a dropping process using a sealant as disclosed in Patent Documents 1 and 2 has been used.

[0003] In the dripping process, first, a frame-shaped seal pattern is formed by dispensing on one of the two substrates with electrodes. Next, tiny droplets of liquid crystal are dripped into the frame of the seal pattern while the sealant is not solidified, and the sealant is solidified after overlapping the other substrate under vacuum to produce a liquid crystal display element. Currently, this dripping process has become the mainstream method for manufacturing liquid crystal display elements.

[0004] However, in the modern era when various mobile devices with liquid crystal panels such as mobile phones and portable game consoles are popular, miniaturization of devices is the most needed issue. As a method for miniaturization of devices, narrow frame of the liquid crystal display part can be cited, for example, the position of the sealing part is arranged under the black matrix (hereinafter also referred to as narrow frame design).

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2001-133794

[0008] Patent document 2: International Publication No. 02 / 092718 Summary of the invention

[0009] Problems to be solved by the invention

[0010] In the narrow frame design, the sealant is arranged directly below the black matrix. Therefore, if the dripping process is performed, the light irradiated during the photocuring of the sealant is blocked, and the light is difficult to reach the inside of the sealant, and the curing of the existing sealant becomes insufficient. In this way, if the curing of the sealant becomes insufficient, there is a problem that the uncured sealant components are dissolved into the liquid crystal and liquid crystal contamination is easily caused. In particular, in recent years, with the high polarity of liquid crystals, liquid crystal contamination sometimes occurs even when using sealants that have not been a problem in the past, and further low liquid crystal contamination properties are required for the sealant.

[0011] When it is difficult to photo-cure the sealant, curing by heating is considered, and as a method for curing the sealant by heating, a thermosetting agent is added to the sealant. However, when a highly reactive thermosetting agent is used to improve the curability and adhesion of the sealant, the storage stability of the obtained sealant may be deteriorated or liquid crystal contamination may occur.

[0012] The present invention aims to provide a novel dihydrazide compound. In addition, the present invention aims to provide a curable resin composition containing the dihydrazide compound and having excellent storage stability, curability and adhesion, and a sealant for a liquid crystal display element, a vertical conductive material and a liquid crystal display element formed by using the curable resin composition and having excellent low liquid crystal contamination.

[0013] Means for solving problems

[0014] The present invention is a dihydrazide compound having a divalent aliphatic hydrocarbon group in which one or more hydrogen atoms are substituted with a group containing an aromatic ring.

[0015] The present invention is described in detail below.

[0016] The present inventors have discovered that by using a dihydrazide compound having a specific structure as a thermosetting agent, a curable resin composition having excellent storage stability, curability and adhesiveness can be obtained, and that a sealant for a liquid crystal display element formed using the curable resin composition also has excellent low liquid crystal contamination properties, thereby completing the present invention.

[0017] The dihydrazide compound of the present invention has a divalent aliphatic hydrocarbon group in which one or more hydrogen atoms are substituted by a group containing an aromatic ring. By using the dihydrazide compound of the present invention having such a structure as a thermosetting agent, a curable resin composition having excellent storage stability, curability and adhesion can be obtained. In addition, the dihydrazide compound of the present invention has low solubility in high-polarity liquid crystals, so the low liquid crystal contamination of the sealant for liquid crystal display elements formed by using the curable resin composition is also further excellent.

[0018] Examples of the group containing an aromatic ring include a phenyl group, a tolyl group, a benzyl group, a chlorophenyl group, a bromophenyl group, an aminophenyl group, a nitrophenyl group, a pyridyl group, a biphenyl group, a methylbiphenyl group, a naphthyl group, and an anthracenyl group.

[0019] Examples of the aliphatic hydrocarbon group include a methylene group, an ethylene group, a propylene group, a butylene group, and a hexenyl group.

[0020] From the viewpoint of achieving both good reactivity and storage stability, the dihydrazide compound of the present invention is preferably represented by the following formula (1).

[0021] Examples of the compound represented by the following formula (1) include phenylsuccinic acid dihydrazide (a compound represented by the following formula (2)), benzylmalonic acid dihydrazide, and phenylmalonic acid dihydrazide.

[0022] Among them, the dihydrazide compound of the present invention is more preferably represented by the following formula (2) from the viewpoint of having steric hindrance capable of reducing liquid crystal contamination.

[0023]

Chemical formula 1

[0024]

[0025] In the formula (1), Ar is a group containing an aromatic ring, m is an integer of 0 to 5, and n is an integer of 0 to 5.

[0026] In addition, the case where m is 0 and the case where n is 0 respectively refer to the case where the carbon atom bonded to Ar is directly bonded to the carbon atom of the carbonyl group in the hydrazide group.

[0027]

Chemical formula 2

[0028]

[0029] As a method for producing the dihydrazide compound of the present invention, for example, the following method etc. can be mentioned.

[0030] Specifically, first, a dicarboxylic acid having a divalent aliphatic hydrocarbon group is heated in methanol under an acidic catalyst and then neutralized to obtain a methyl ester derivative. Hydrazine is added to the obtained reactant in methanol to react, thereby obtaining the dihydrazide compound of the present invention.

[0031] Examples of the dicarboxylic acid include phenylmalonic acid, tolylmalonic acid, phenylsuccinic acid, tolylsuccinic acid, benzylmalonic acid, benzylsuccinic acid, 2-phenylglutaric acid, 3-phenylglutaric acid, 2-benzylglutaric acid, 3-benzylglutaric acid, 2-phenyladipic acid, 3-phenyladipic acid, 2-benzyladipic acid, and 3-benzyladipic acid.

[0032] The dihydrazide compound of the present invention is suitably used as a thermosetting agent to be blended in a curable resin composition.

[0033] A curable resin composition comprising a curable resin and a thermosetting agent, wherein the thermosetting agent comprises the dihydrazide compound of the present invention, is also one of the present invention.

[0034] Relative to 100 parts by weight of curable resin, the preferred lower limit of the content of the dihydrazide compound of the present invention is 3 parts by weight, and the preferred upper limit is 20 parts by weight. By making the content of the dihydrazide compound of the present invention more than 3 parts by weight, the curability and adhesion of the obtained curable resin composition are more excellent. By making the content of the dihydrazide compound of the present invention less than 20 parts by weight, the storage stability of the obtained curable resin composition is more excellent, and, in the case of a sealant for a liquid crystal display element, low liquid crystal contamination becomes more excellent. The more preferred lower limit of the content of the dihydrazide compound of the present invention is 5 parts by weight, and the more preferred upper limit is 15 parts by weight.

[0035] The curable resin composition of the present invention may contain other thermosetting agents in addition to the dihydrazide compound of the present invention within a range not inhibiting the purpose of the present invention.

[0036] Examples of the thermosetting agent include organic acid hydrazides other than the dihydrazide compound of the present invention, imidazole derivatives, amine compounds, polyphenol compounds, and acid anhydrides.

[0037] The curable resin composition of the present invention contains a curable resin.

[0038] The curable resin preferably contains an epoxy compound.

[0039] Examples of the epoxy compound include bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol E epoxy resin, bisphenol S epoxy resin, 2,2′-diallylbisphenol A epoxy resin, hydrogenated bisphenol epoxy resin, propylene oxide-added bisphenol A epoxy resin, resorcinol epoxy resin, biphenyl epoxy resin, sulfide epoxy resin, diphenyl ether epoxy resin, dicyclopentadiene epoxy resin, naphthalene epoxy resin, phenol novolac epoxy resin, o-cresol novolac epoxy resin, dicyclopentadiene novolac epoxy resin, biphenyl novolac epoxy resin, naphthol novolac epoxy resin, glycidylamine epoxy resin, alkyl polyol epoxy resin, rubber-modified epoxy resin, and glycidyl ester compounds.

[0040] As what is marketed among the said bisphenol A type epoxy resins, jER828EL, jER1004 (all are manufactured by Mitsubishi Chemical Corporation), EPICLON850 (manufactured by DIC Corporation), etc. are mentioned, for example.

[0041] As what is marketed among the said bisphenol F type epoxy resins, jER806, jER4004 (all are manufactured by Mitsubishi Chemical Corporation), EPICLON EXA-830CRP (manufactured by DIC Corporation), etc. are mentioned, for example.

[0042] As what is marketed among the said bisphenol E type epoxy resins, EPOMIK R710 (made by Mitsui Chemicals, Inc.) etc. are mentioned, for example.

[0043] As what is marketed among the said bisphenol S type epoxy resin, EPICLON EXA-1514 (made by DIC Corporation) etc. are mentioned, for example.

[0044] As what is marketed among the said 2, 2'- diallyl bisphenol A type epoxy resin, RE-810NM (made by Nippon Kayaku Co., Ltd.) etc. are mentioned, for example.

[0045] As what is marketed among the said hydrogenated bisphenol type epoxy resin, EPICLON EXA-7015 (made by DIC Corporation) etc. are mentioned, for example.

[0046] As what is marketed among the said propylene oxide addition bisphenol A type epoxy resin, EP-4000S (made by ADEKA Corporation) etc. are mentioned, for example.

[0047] As what is marketed among the said resorcinol type epoxy resins, EX-201 (made by Nagase ChemteX Co., Ltd.) etc. are mentioned, for example.

[0048] As what is marketed among the said biphenyl type epoxy resin, jER YX-4000H (made by Mitsubishi Chemical Corporation) etc. are mentioned, for example.

[0049] As what is marketed among the said thioether type epoxy resins, YSLV-50TE (made by NIPPON STEEL Chemical & Material Co., Ltd.) etc. are mentioned, for example.

[0050] As what is marketed among the said diphenyl ether type epoxy resins, YSLV-80DE (made by NIPPON STEEL Chemical & Material Co., Ltd.) etc. are mentioned, for example.

[0051] As what is marketed among the said dicyclopentadiene type epoxy resin, EP-4088S (made by ADEKA Corporation) etc. are mentioned, for example.

[0052] As what is marketed among the said naphthalene type epoxy resin, EPICLON HP-4032, EPICLON EXA-4700 (all are manufactured by DIC Corporation), etc. are mentioned, for example.

[0053] As what is marketed among the said phenol novolac-type epoxy resins, EPICLON N-770 (made by DIC Corporation) etc. are mentioned, for example.

[0054] As what is marketed among the said o-cresol novolac-type epoxy resins, EPICLON N-670-EXP-S (made by DIC Corporation) etc. are mentioned, for example.

[0055] As what is marketed among the said dicyclopentadiene novolak-type epoxy resins, EPICLON HP-7200 (made by DIC Corporation) etc. are mentioned, for example.

[0056] As what is marketed among the said biphenyl novolak-type epoxy resins, NC-3000P (made by Nippon Kayaku Co., Ltd.) etc. are mentioned, for example.

[0057] As what is marketed among the said naphthol novolak-type epoxy resins, ESN-165S (made by NIPPON STEEL Chemical & Material Co., Ltd.) etc. are mentioned, for example.

[0058] Examples of commercially available products of the glycidylamine epoxy resins include jER630 (manufactured by Mitsubishi Chemical Corporation), EPICLON 430 (manufactured by DIC Corporation), and TETRAD-X (manufactured by Mitsubishi Gas Chemical Corporation).

[0059] Examples of commercially available products of the alkyl polyol epoxy resins include ZX-1542 (manufactured by Nippon Steel Chemical & Material Co., Ltd.), Epiclon 726 (manufactured by DIC Corporation), Epolight 80MFA (manufactured by Kyoeisha Chemical Co., Ltd.), and Denacol EX-611 (manufactured by Nagase ChemteX Corporation).

[0060] Examples of commercially available products of the rubber-modified epoxy resin include YR-450 and YR-207 (both manufactured by NIPPON STEEL Chemical & Material Co., Ltd.) and Epolead PB (manufactured by DAICEL Co., Ltd.).

[0061] As a commercial item among the said glycidyl ester compound, Denacol EX-147 (made by Nagase ChemteX) etc. are mentioned, for example.

[0062] As other commercially available products of the above-mentioned epoxy compounds, for example, YDC-1312, YSLV-80XY, YSLV-90CR (all manufactured by NIPPON STEEL Chemical & Material Co., Ltd.), XAC4151 (manufactured by Asahi Kasei Corporation), jER1031, jER1032 (all manufactured by Mitsubishi Chemical Corporation), EXA-7120 (manufactured by DIC Corporation), TEPIC (manufactured by Nissan Chemical Co., Ltd.), etc. can be mentioned.

[0063] As the epoxy compound, a partially (meth)acrylic acid-modified epoxy resin can also be suitably used.

[0064] In the present specification, the partially (meth)acrylic acid-modified epoxy resin refers to a compound having one or more epoxy groups and one or more (meth)acryloyl groups in one molecule, which can be obtained by reacting a part of epoxy groups of an epoxy compound having two or more epoxy groups with (meth)acrylic acid.

[0065] In addition, in this specification, the said "(meth)acrylic acid" means acrylic acid or methacrylic acid, and the said "(meth)acryloyl group" means acryloyl group or methacryloyl group.

[0066] As what is marketed among the said partial (meth)acryl-modified epoxy resin, UVACURE1561, KRM8287 (all are manufactured by DAICEL ALLNEX CO., LTD.) etc. are mentioned, for example.

[0067] Furthermore, the curable resin may contain a (meth)acrylic compound.

[0068] Examples of the (meth)acrylic compound include (meth)acrylate compounds, epoxy (meth)acrylates, and urethane (meth)acrylates. Among them, epoxy (meth)acrylates are preferred. In addition, from the viewpoint of reactivity, the (meth)acrylic compound preferably has two or more (meth)acryloyl groups in one molecule.

[0069] It should be noted that, in this specification, the above-mentioned "(meth)acrylic compound" refers to a compound having a (meth)acryloyl group. In addition, the above-mentioned "(meth)acrylate" refers to acrylate or methacrylate, and the above-mentioned "epoxy (meth)acrylate" refers to a compound obtained by reacting all epoxy groups in an epoxy compound with (meth)acrylic acid.

[0070] Examples of the monofunctional compound among the (meth)acrylate compounds include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, isomyristyl (meth)acrylate, stearyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentenyl (meth)acrylate, benzyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-Butoxyethyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, methoxyethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, ethyl carbitol (meth)acrylate, 2,2,2-trifluoroethyl (meth)acrylate, 2,2,3,3-tetrafluoropropyl (meth)acrylate, 1H,1H,5H-octafluoropentyl (meth)acrylate, imide (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, 2-(meth)acryloyloxyethyl succinic acid, 2-(meth)acryloyloxyethyl hexahydrophthalic acid, 2-(meth)acryloyloxyethyl 2-hydroxypropyl phthalate, 2-(meth)acryloyloxyethyl phosphate, glycidyl (meth)acrylate, and the like.

[0071] Examples of the bifunctional compound among the (meth)acrylate compounds include 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, 2-n-butyl-2-ethyl-1,3-propanediol di(meth)acrylate, dipropylene glycol di(meth)acrylate, and tripropylene glycol di(meth)acrylate. , polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, ethylene oxide added bisphenol A di(meth)acrylate, propylene oxide added bisphenol A di(meth)acrylate, ethylene oxide added bisphenol F di(meth)acrylate, dihydroxymethyl dicyclopentadienyl di(meth)acrylate, ethylene oxide modified isocyanuric acid di(meth)acrylate, 2-hydroxy-3-(meth)acryloxypropyl (meth)acrylate, carbonate diol di(meth)acrylate, polyether diol di(meth)acrylate, polyester diol di(meth)acrylate, polycaprolactone diol di(meth)acrylate, polybutadiene diol di(meth)acrylate, etc.

[0072] Examples of the trifunctional or higher-functional (meth)acrylate compounds include trimethylolpropane tri(meth)acrylate, ethylene oxide-added trimethylolpropane tri(meth)acrylate, propylene oxide-added trimethylolpropane tri(meth)acrylate, caprolactone-modified trimethylolpropane tri(meth)acrylate, ethylene oxide-added isocyanuric acid tri(meth)acrylate, glycerol tri(meth)acrylate, propylene oxide-added glycerol tri(meth)acrylate, pentaerythritol tri(meth)acrylate, tri(meth)acryloyloxyethyl phosphate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, and dipentaerythritol hexa(meth)acrylate.

[0073] Examples of the epoxy (meth)acrylate include epoxy (meth)acrylates obtained by reacting an epoxy compound with (meth)acrylic acid in the presence of a basic catalyst according to a conventional method.

[0074] As the epoxy compound used as a raw material for synthesizing the epoxy (meth)acrylate, the same epoxy compound as the above-mentioned epoxy compound as the curable resin contained in the curable resin composition of the present invention can be used.

[0075] Examples of commercially available products of the epoxy (meth)acrylate include epoxy (meth)acrylate manufactured by Daicel Allnex, epoxy (meth)acrylate manufactured by Shin-Nakamura Chemical Industry Co., Ltd., epoxy (meth)acrylate manufactured by Kyoeisha Chemical Co., Ltd., and epoxy (meth)acrylate manufactured by Nagase ChemteX.

[0076] Examples of the epoxy (meth)acrylate manufactured by DAICEL ALLNEX include EBECRYL 860, EBECRYL 3200, EBECRYL 3201, EBECRYL 3412, EBECRYL 3600, EBECRYL 3700, EBECRYL 3701, EBECRYL 3702, EBECRYL 3703, EBECRYL 3708, EBECRYL 3800, EBECRYL 6040, and EBECRYL RDX63182.

[0077] As said epoxy (meth)acrylate manufactured by Shin-Nakamura Chemical Industry Co., Ltd., EA-1010, EA-1020, EA-5323, EA-5520, EA-CHD, EMA-1020 etc. are mentioned, for example.

[0078] Examples of the epoxy (meth)acrylate manufactured by Kyoeisha Chemical Co., Ltd. include Epoxy Ester M-600A, Epoxy Ester 40EM, Epoxy Ester 70PA, Epoxy Ester 200PA, Epoxy Ester 80MFA, Epoxy Ester 3002M, Epoxy Ester 3002A, Epoxy Ester 1600A, Epoxy Ester 3000M, Epoxy Ester 3000A, Epoxy Ester 200EA, and Epoxy Ester 400EA.

[0079] As said Nagase ChemteX epoxy (meth)acrylate, Denacol Acrylate DA-141, Denacol Acrylate DA-314, Denacol Acrylate DA-911 etc. are mentioned, for example.

[0080] The urethane (meth)acrylate may be obtained, for example, by reacting a (meth)acrylic acid derivative having a hydroxyl group with an isocyanate compound in the presence of a catalytic amount of a tin-based compound.

[0081] Examples of the isocyanate compound used as a raw material for the urethane (meth)acrylate include isophorone diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, diphenylmethane-4,4′-diisocyanate (MDI), hydrogenated MDI, polymeric MDI, 1,5-naphthalene diisocyanate, norbornane diisocyanate, tolidine diisocyanate, xylylene diisocyanate (XDI), hydrogenated XDI, lysine diisocyanate, triphenylmethane triisocyanate, tris(isocyanatephenyl)phosphorothioate, tetramethylxylylene diisocyanate, and 1,6,11-undecane triisocyanate.

[0082] Furthermore, as the isocyanate compound serving as a raw material of the urethane (meth)acrylate, a chain-extended isocyanate compound obtained by a reaction between a polyol and an excess of an isocyanate compound may be used.

[0083] Examples of the polyol include ethylene glycol, propylene glycol, glycerin, sorbitol, trimethylolpropane, carbonate diol, polyether diol, polyester diol, and polycaprolactone diol.

[0084] Examples of the (meth)acrylic acid derivative having a hydroxyl group include hydroxyalkyl mono(meth)acrylates, mono(meth)acrylates of diols, mono(meth)acrylates or di(meth)acrylates of triols, and epoxy(meth)acrylates.

[0085] Examples of the hydroxyalkyl mono(meth)acrylate include 2-hydroxyethyl(meth)acrylate, 2-hydroxypropyl(meth)acrylate, 2-hydroxybutyl(meth)acrylate, and 4-hydroxybutyl(meth)acrylate.

[0086] Examples of the diol include ethylene glycol, propylene glycol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, and polyethylene glycol.

[0087] Examples of the triol include trimethylolethane, trimethylolpropane, and glycerin.

[0088] As said epoxy (meth)acrylate, bisphenol A type epoxy acrylate etc. are mentioned, for example.

[0089] Examples of commercially available products of the urethane (meth)acrylates include urethane (meth)acrylate manufactured by Toagosei Co., Ltd., urethane (meth)acrylate manufactured by Daicel Allnex Co., Ltd., urethane (meth)acrylate manufactured by Negami Industries Co., Ltd., urethane (meth)acrylate manufactured by Shin-Nakamura Chemical Co., Ltd., and urethane (meth)acrylate manufactured by Kyoeisha Chemical Co., Ltd.

[0090] As the urethane (meth)acrylate manufactured by Toagosei Co., Ltd., for example, M-1100, M-1200, M-1210, and M-1600 can be mentioned.

[0091] Examples of the urethane (meth)acrylate manufactured by DAICEL ALLNEX include EBECRYL 210, EBECRYL 220, EBECRYL 230, EBECRYL 270, EBECRYL 1290, EBECRYL 2220, EBECRYL 4827, EBECRYL 4842, EBECRYL 4858, EBECRYL 5129, EBECRYL 6700, EBECRYL 8402, EBECRYL 8803, EBECRYL 8804, EBECRYL 8807, and EBECRYL 9260.

[0092] Examples of the urethane (meth)acrylate manufactured by Negami Industries include Art Resin UN-330, Art Resin SH-500B, Art Resin UN-1200TPK, Art Resin UN-1255, Art Resin UN-3320HB, Art Resin UN-7100, Art Resin UN-9000A, and Art Resin UN-9000H.

[0093] Examples of the urethane (meth) acrylate manufactured by Shin-Nakamura Chemical Industry Co., Ltd. include U-2HA, U-2PHA, U-3HA, U-4HA, U-6H, U-6HA, U-6LPA, U-10H, U-15HA, U-108, U-108A, U-122A, U-122P, U-324A, U-340A, U-340P, U-1084A, U-2061BA, UA-340P, UA-4000, UA-4100, UA-4200, UA-4400, UA-5201P, UA-7100, UA-7200, and UA-W2A.

[0094] Examples of the urethane (meth)acrylate manufactured by Kyoeisha Chemical Co., Ltd. include AH-600, AI-600, AT-600, UA-101I, UA-101T, UA-306H, UA-306I, and UA-306T.

[0095] When the curable resin contains the (meth) acrylic acid compound in addition to the epoxy compound, or when the curable resin contains the partially (meth) acrylic acid-modified epoxy compound, the ratio of the (meth) acryloyl group in the total of the epoxy group and the (meth) acryloyl group in the curable resin is preferably 30 mol% or more and 95 mol% or less. By setting the ratio of the (meth) acryloyl group to be within this range, the curable resin composition obtained has better adhesion and, when used in a sealant for a liquid crystal display element, has better low liquid crystal contamination.

[0096] From the viewpoint of further suppressing liquid crystal contamination, the curable resin preferably has a hydrogen-bonding unit such as an -OH group, an -NH- group, or an -NH2 group.

[0097] The curable resin composition of the present invention preferably further contains a photoradical polymerization initiator.

[0098] Examples of the photoradical polymerization initiator include benzophenone compounds, acetophenone compounds, acylphosphine oxide compounds, titanocene compounds, oxime ester compounds, benzoin ether compounds, and thioxanthone compounds.

[0099] Specific examples of the photoradical polymerization initiator include 1-hydroxycyclohexyl phenyl ketone, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-1-butanone, 2-(dimethylamino)-2-((4-methylphenyl)methyl)-1-(4-(4-morpholino)phenyl)-1-butanone, 2,2-dimethoxy-1,2-diphenylethane-1-one, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropane-1-one, 1-(4-(2-hydroxyethoxy)-phenyl)-2-hydroxy-2-methyl-1-propane-1-one, 1-(4-(phenylthio)phenyl)-1,2-octanedione 2-(O-benzoyloxime), and 2,4,6-trimethylbenzoyldiphenylphosphine oxide.

[0100] The above-mentioned radical photopolymerization initiators may be used alone or in combination of two or more.

[0101] The preferred lower limit of the content of the above-mentioned free radical polymerization initiator is 0.5 parts by weight, and the preferred upper limit is 10 parts by weight relative to 100 parts by weight of the above-mentioned curable resin. By making the content of the above-mentioned free radical polymerization initiator within this range, the storage stability and photocurability of the obtained curable resin composition are more excellent, and the low liquid crystal contamination when used as a sealant for liquid crystal display elements is more excellent. The more preferred lower limit of the content of the above-mentioned free radical polymerization initiator is 1 part by weight, and the more preferred upper limit is 7 parts by weight.

[0102] The curable resin composition of the present invention may contain a thermal radical polymerization initiator.

[0103] As the above-mentioned thermal radical polymerization initiator, for example, thermal radical polymerization initiators composed of azo compounds, organic peroxides, etc. can be mentioned. Among them, from the viewpoint of suppressing liquid crystal contamination when the obtained curable resin composition is used as a sealant for liquid crystal display elements, an initiator composed of an azo compound (hereinafter also referred to as "azo initiator") is preferred, and an initiator composed of a polymer azo compound (hereinafter also referred to as "polymer azo initiator") is more preferred.

[0104] The above-mentioned thermal radical polymerization initiators may be used alone or in combination of two or more.

[0105] In addition, in this specification, the said "polymer azo compound" refers to the compound which has an azo group, generates the radical which can cure a (meth)acryloyl group by heat, and has a number average molecular weight of 300 or more.

[0106] The preferred lower limit of the number average molecular weight of the polymer azo compound is 1000, and the preferred upper limit is 300,000. By making the number average molecular weight of the polymer azo compound within this range, it is possible to prevent the adverse effects on liquid crystal when the obtained curable resin composition is used as a sealant for liquid crystal display elements, and it can be easily mixed into the curable resin. The more preferred lower limit of the number average molecular weight of the polymer azo compound is 5000, the more preferred upper limit is 100,000, the further preferred lower limit is 10,000, and the further preferred upper limit is 90,000.

[0107] It should be noted that in this specification, the number average molecular weight is a value obtained by measuring the sample concentration at a flow rate of 1 mL / min using gel permeation chromatography (GPC) in a tetrahydrofuran solution of 0.5% by weight. GPC can use, for example, HPLC-9210 2NEXT (Japan Analytical Industry Co., Ltd.), and as the column used in GPC, for example, JAIGEL2H (Japan Analytical Industry Co., Ltd.) can be cited.

[0108] Examples of the polymer azo compound include polymer azo compounds having a structure in which a plurality of units of polyalkylene oxide, polydimethylsiloxane, or the like are bonded via an azo group.

[0109] As the polymer azo compound having a structure in which a plurality of units such as polyalkylene oxide are bonded via an azo group, a polymer azo compound having a polyethylene oxide structure is preferred.

[0110] Specific examples of the polymer azo compound include a polycondensate of 4,4′-azobis(4-cyanovaleric acid) and polyalkylene glycol, and a polycondensate of 4,4′-azobis(4-cyanovaleric acid) and polydimethylsiloxane having a terminal amino group.

[0111] Examples of commercially available products of the polymer azo initiator include VPE-0201, VPE-0401, VPE-0601, VPS-0501, and VPS-1001 (all manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.).

[0112] Examples of non-polymeric azo initiators include V-65 and V-501 (both manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.).

[0113] Examples of the organic peroxide include ketone peroxide, peroxyketal, hydroperoxide, dialkyl peroxide, peroxyester, diacyl peroxide, and peroxydicarbonate.

[0114] Relative to 100 parts by weight of the curable resin, the preferred lower limit of the content of the thermal free radical polymerization initiator is 0.1 parts by weight, and the preferred upper limit is 10 parts by weight. By making the content of the thermal free radical polymerization initiator within this range, the storage stability and thermosetting properties of the obtained curable resin composition are more excellent, and the low liquid crystal contamination when used for a sealant for a liquid crystal display element is more excellent. The more preferred lower limit of the content of the thermal free radical polymerization initiator is 0.3 parts by weight, and the more preferred upper limit is 5 parts by weight.

[0115] The curable resin composition of the present invention may contain a filler for the purpose of improving viscosity, improving adhesion due to a stress dispersion effect, improving linear expansion coefficient, improving moisture resistance of a cured product, and the like.

[0116] As the filler, an inorganic filler or an organic filler can be used.

[0117] Examples of the inorganic filler include silica, talc, glass beads, asbestos, gypsum, diatomaceous earth, smectite, bentonite, montmorillonite, sericite, activated clay, aluminum oxide, zinc oxide, iron oxide, magnesium oxide, tin oxide, titanium oxide, calcium carbonate, magnesium carbonate, magnesium hydroxide, aluminum hydroxide, aluminum nitride, silicon nitride, barium sulfate, and calcium silicate.

[0118] Examples of the organic filler include polyester microparticles, polyurethane microparticles, vinyl polymer microparticles, and acrylic polymer microparticles.

[0119] The above-mentioned fillers may be used alone or in combination of two or more.

[0120] The preferred lower limit of the content of the filler in 100 parts by weight of the curable resin composition of the present invention is 10 parts by weight, and the preferred upper limit is 70 parts by weight. By making the content of the filler within this range, the coating property and the like will not be deteriorated, and the effects of improving the adhesiveness and the like will become more excellent. The more preferred lower limit of the content of the filler is 20 parts by weight, and the more preferred upper limit is 60 parts by weight.

[0121] The curable resin composition of the present invention may contain a silane coupling agent. The silane coupling agent mainly functions as an adhesion aid for favorably bonding the curable resin composition to a substrate or the like.

[0122] As the above-mentioned silane coupling agent, for example, 3-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-isocyanatepropyltrimethoxysilane, etc. are preferably used. They are excellent in the effect of improving the adhesion to the substrate, etc., and when the obtained curable resin composition is used as a sealant for liquid crystal display elements, the outflow of the curable resin into the liquid crystal can be suppressed.

[0123] The above-mentioned silane coupling agents may be used alone or in combination of two or more.

[0124] The preferred lower limit of the content of the above-mentioned silane coupling agent in 100 parts by weight of the curable resin composition of the present invention is 0.1 parts by weight, and the preferred upper limit is 10 parts by weight. By making the content of the above-mentioned silane coupling agent within this range, the effect of improving the adhesiveness is more excellent, and when the obtained curable resin composition is used for a sealant for a liquid crystal display element, the low liquid crystal contamination property becomes more excellent. The more preferred lower limit of the content of the above-mentioned silane coupling agent is 0.3 parts by weight, and the more preferred upper limit is 5 parts by weight.

[0125] The curable resin composition of the present invention may contain a light-shielding agent. By containing the light-shielding agent, the curable resin composition of the present invention can be suitably used as a light-shielding sealant.

[0126] Examples of the light-shielding agent include iron oxide, titanium black, aniline black, cyanine black, fullerene, carbon black, and resin-coated carbon black. Among them, titanium black is preferred.

[0127] The titanium black is a substance whose transmittance to light near the ultraviolet region, especially light with a wavelength of 370 nm or more and 450 nm or less, is higher than the average transmittance to light with a wavelength of 300 nm or more and 800 nm or less. That is, the titanium black is a light-shielding agent having the property of imparting light-shielding properties to the curable resin composition of the present invention by fully shielding light with a wavelength in the visible light region, and on the other hand, transmitting light with a wavelength near the ultraviolet region. Therefore, as the above-mentioned photo-radical polymerization initiator, by using a photo-radical polymerization initiator that can initiate a reaction due to light with a wavelength that increases the transmittance of the titanium black, the photocurability of the curable resin composition of the present invention can be further increased. In addition, on the other hand, as the light-shielding agent contained in the curable resin composition of the present invention, a substance with high insulating properties is preferred, and as a light-shielding agent with high insulating properties, titanium black is also suitable.

[0128] The optical density (OD value) per 1 μm of the titanium black is preferably 3 or more, more preferably 4 or more. The higher the light shielding property of the titanium black, the better. There is no particularly preferred upper limit for the OD value of the titanium black, but it is usually 5 or less.

[0129] The titanium black described above can fully exert its effect even without surface treatment, but titanium black whose surface has been treated with an organic component such as a coupling agent, or titanium black coated with an inorganic component such as silicon oxide, titanium oxide, germanium oxide, aluminum oxide, zirconium oxide, magnesium oxide, etc., which has been surface treated, can also be used. Among them, titanium black treated with an organic component is preferred from the viewpoint of further improving insulation.

[0130] Furthermore, a display element produced using the curable resin composition of the present invention blended with the titanium black as a light-shielding agent has sufficient light-shielding properties, and thus can realize a display element having high contrast without light leakage and excellent image display quality.

[0131] Examples of commercially available products of the titanium black include titanium black manufactured by Mitsubishi Materials Corporation and titanium black manufactured by Ako Chemicals Co., Ltd.

[0132] Examples of the titanium black manufactured by Mitsubishi Materials Corporation include 12S, 13M, 13M-C, 13R-N, and 14M-C.

[0133] As the titanium black manufactured by Ako Chemicals Co., Ltd., for example, Tilack D etc. can be mentioned.

[0134] The preferred lower limit of the specific surface area of ​​the titanium black is 13 m 2 / g, the preferred upper limit is 30m2 / g, and a more preferred lower limit is 15m 2 / g, and the more preferred upper limit is 25m 2 / g.

[0135] The preferred lower limit of the volume resistivity of the titanium black is 0.5 Ω·cm, the preferred upper limit is 3 Ω·cm, the more preferred lower limit is 1 Ω·cm, and the more preferred upper limit is 2.5 Ω·cm.

[0136] The preferred lower limit of the primary particle size of the above-mentioned light-shielding agent is 1 nm, and the preferred upper limit is 5000 nm. By making the primary particle size of the above-mentioned light-shielding agent within this range, the light-shielding property can be made more excellent without deteriorating the coating property of the obtained curable resin composition. The more preferred lower limit of the primary particle size of the above-mentioned light-shielding agent is 5 nm, the more preferred upper limit is 200 nm, the further preferred lower limit is 10 nm, and the further preferred upper limit is 100 nm.

[0137] The primary particle size of the light-shielding agent can be measured by dispersing the light-shielding agent in a solvent (water, an organic solvent, etc.) using NICOMP380ZLS (manufactured by PARTICLE SIZING SYSTEMS).

[0138] The preferred lower limit of the content of the above-mentioned light-shielding agent in 100 parts by weight of the curable resin composition of the present invention is 5 parts by weight, and the preferred upper limit is 80 parts by weight. By making the content of the above-mentioned light-shielding agent within this range, it is possible to exert a more excellent light-shielding property without significantly reducing the adhesion, strength and drawing properties of the obtained curable resin composition after curing. The more preferred lower limit of the content of the above-mentioned light-shielding agent is 10 parts by weight, the more preferred upper limit is 70 parts by weight, the further preferred lower limit is 30 parts by weight, and the further preferred upper limit is 60 parts by weight.

[0139] The curable resin composition of the present invention may further contain additives such as a stress relaxant, a reactive diluent, a thixotropic agent, a spacer, a curing accelerator, a defoaming agent, a leveling agent, and a polymerization inhibitor as required.

[0140] Examples of a method for producing the curable resin composition of the present invention include a method of mixing a curable resin, a thermosetting agent, and, if necessary, a photoradical polymerization initiator, etc. using a mixer.

[0141] Examples of the mixer include a homodisperser, a homomixer, a universal mixer, a planetary mixer, a kneader, and a three-roll mill.

[0142] The curable resin composition of the present invention is suitably used as a sealant for display elements, and is particularly suitably used as a sealant for liquid crystal display elements. A sealant for liquid crystal display elements formed by using the curable resin composition of the present invention is also one of the present invention.

[0143] By mixing conductive fine particles in the sealing agent for liquid crystal display elements of the present invention, a vertical conduction material can be produced. Such a vertical conduction material containing the sealing agent for liquid crystal display elements of the present invention and conductive fine particles is also one of the present invention.

[0144] As the conductive particles, for example, metal balls, conductive particles having a conductive metal layer formed on the surface of resin particles, etc. can be used. Among them, particles having a conductive metal layer formed on the surface of resin particles are suitable because they can be electrically connected without damaging a transparent substrate due to the excellent elasticity of the resin particles.

[0145] A liquid crystal display element formed by using the sealing agent for a liquid crystal display element of the present invention or the vertical conduction material of the present invention is also one of the present invention.

[0146] The sealing agent for liquid crystal display elements of the present invention has low compatibility with liquid crystal molecules having polar groups, so when the liquid crystal display element of the present invention is formed using liquid crystals containing liquid crystal molecules having polar groups, the effect of suppressing display defects becomes more significant compared to conventional sealing agents. That is, the liquid crystal display element of the present invention is preferably formed using liquid crystals containing liquid crystal molecules having polar groups.

[0147] Examples of the polar group of the liquid crystal molecule include a fluorine group, a chlorine group, and a cyano group.

[0148] The liquid crystal display element of the present invention is preferably a liquid crystal display element of narrow frame design. Specifically, the width of the frame portion around the liquid crystal display part is preferably 2 mm or less.

[0149] Moreover, the coating width of the curable resin composition of this invention at the time of manufacturing the liquid crystal display element of this invention is preferably 1 mm or less.

[0150] The sealing agent for liquid crystal display elements of this invention can be used suitably for manufacture of a liquid crystal display element by a liquid crystal dropping method.

[0151] As a method of manufacturing the liquid crystal display element of this invention by a liquid crystal dropping process, the following method etc. are mentioned, for example.

[0152] First, a process of forming a frame-shaped seal pattern on a substrate by screen printing, dispenser coating, etc. is performed with the sealant for the liquid crystal display element of the present invention. Next, a small drop of liquid crystal is applied to the entire surface of the frame of the seal pattern in an uncured state of the sealant for the liquid crystal display element of the present invention, and another substrate is immediately overlapped. Then, a liquid crystal display element can be obtained by performing a process of heating the sealant to cure it. In addition, a process of irradiating the seal pattern portion with light such as ultraviolet rays to pre-cure the sealant can be performed before the process of heating the sealant to cure it.

[0153] Effects of the Invention

[0154] According to the present invention, a novel dihydrazide compound can be provided. In addition, the present invention can provide a curable resin composition containing the dihydrazide compound and having excellent storage stability, curability and adhesion, and a sealant for liquid crystal display elements, a vertical conductive material and a liquid crystal display element formed by using the curable resin composition and having excellent low liquid crystal contamination. DETAILED DESCRIPTION

[0155] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.

[0156] (Synthesis Example 1 (Synthesis of phenylsuccinic acid dihydrazide))

[0157] In an eggplant-shaped flask, 19.4 g of phenylsuccinic acid and 0.49 g of sulfuric acid were added to 50 mL of methanol, and the mixture was reacted under reflux for 10 hours. After the reaction solution was cooled to room temperature, 1.11 g of triethylamine was added for neutralization, and 20.0 g of hydrazine monohydrate was further added, and the mixture was reacted at 25° C. for 6 hours. The precipitate was recovered by filtration using a Kiriyama funnel, washed with methanol, and then vacuum dried to obtain phenylsuccinic acid dihydrazide (the compound represented by the above formula (2)).

[0158] It should be noted that the structure of the obtained phenylsuccinic acid dihydrazide is 1 The results were confirmed by H-NMR, MS and FT-IR.

[0159] (Synthesis Example 2 (Synthesis of benzylmalonic acid dihydrazide))

[0160] Benzylmalonic acid dihydrazide (a compound in which Ar is a benzyl group, m is 0, and n is 0 in the above formula (1)) was obtained in the same manner as in Synthesis Example 1 except that 19.4 g of phenylsuccinic acid was changed to 19.4 g of benzylmalonic acid.

[0161] It should be noted that the structure of the obtained benzylmalonic acid dihydrazide is 1 The results were confirmed by H-NMR, MS and FT-IR.

[0162] (Synthesis Example 3 (Synthesis of phenylmalonic acid dihydrazide))

[0163] Phenylmalonic acid dihydrazide (a compound in which Ar is phenyl, m is 0, and n is 0 in the above formula (1)) was obtained in the same manner as in Synthesis Example 1 except that 19.4 g of phenylsuccinic acid was changed to 18.0 g of phenylmalonic acid.

[0164] It should be noted that the structure of the obtained phenylmalonic acid dihydrazide is 1 The results were confirmed by H-NMR, MS and FT-IR.

[0165] (Examples 1 to 5, Comparative Examples 1 to 3)

[0166] The respective materials were mixed according to the mixing ratios described in Table 1 using a planetary mixer ("Defoam Rentaro" manufactured by THINKY Corporation) and further mixed using a three-roll mill to prepare the respective curable resin compositions of Examples 1 to 5 and Comparative Examples 1 to 3.

[0167] <Evaluation>

[0168] The following evaluations were performed on each of the curable resin compositions obtained in Examples and Comparative Examples.

[0169] (Storage stability)

[0170] For each curable resin composition obtained in the examples and comparative examples, the initial viscosity immediately after production and the viscosity after storage at 25° C. for one week after production were measured. (Viscosity after storage) / (initial viscosity) was taken as the viscosity increase ratio, and the case of the viscosity increase ratio less than 1.05 was recorded as "○", the case of 1.05 or more and less than 1.10 was recorded as "△", and the case of 1.10 or more was recorded as "×", and the storage stability was evaluated.

[0171] The viscosity of the curable resin composition was measured using an E-type viscometer (manufactured by Brook Field, “DV-III”) at 25° C. and a rotation speed of 1.0 rpm.

[0172] (Curing property)

[0173] Each curable resin composition obtained in the examples and comparative examples was irradiated with 100 mW / cm2 of a metal halide lamp for 30 seconds. 2After the ultraviolet rays were applied, the reaction rate of the epoxy group (the reduction rate of the peak from the epoxy group) when it was heated at 120°C for 1 hour to be cured was measured using an infrared spectrometer. The case where the reaction rate was 90% or more was marked as "○", the case where it was 80% or more and less than 90% was marked as "△", and the case where it was less than 80% was marked as "×" to evaluate the curability.

[0174] In addition, UMA600 (made by Agilent Technologies) was used as an infrared spectrometer.

[0175] (Adhesion)

[0176] Each curable resin composition obtained in the examples and comparative examples was filled into a syringe for dispensing (Musashi Engineering, "PSY-10E") and degassed. The degassed curable resin composition was dispensed with a dispenser (Musashi Engineering, "SHOTMASTER300") to the inner four sides 30 mm from the end of a glass substrate (150 mm × 150 mm), and another glass substrate (110 mm × 110 mm) was overlapped and bonded under vacuum. A metal halide lamp was used to irradiate at 100 mW / cm 2 The curable resin composition was pre-cured by irradiating ultraviolet rays for 30 seconds, and then heated at 120°C for 1 hour to thermally cure the curable resin composition to obtain an adhesive test piece. When a metal rod with a radius of 5 mm was pressed into the end of the substrate of the obtained adhesive test piece at a speed of 5 mm / min, the strength (kgf) when panel peeling occurred was measured, and the adhesive force (kg / cm) was calculated.

[0177] Adhesion was evaluated by indicating that the adhesive strength was 150 kg / cm or more as "○", the adhesive strength was 100 kg / cm or more and less than 150 kg / cm as "△", and the adhesive strength was less than 100 kg / cm as "×".

[0178] (Low liquid crystal contamination)

[0179] 1 part by weight of spacer particles (made by Sekisui Chemical Co., Ltd., "Micropearl SI-H050") with an average particle size of 5 μm is dispersed in 100 parts by weight of each curable resin composition obtained in the examples and comparative examples, filled into a syringe, and degassed using a centrifugal degasser (Awatron AW-1). Using a dispenser, the curable resin composition after degassing is applied in a frame shape to one of two substrates with an oriented film and ITO under the conditions of a nozzle diameter of 0.4 mmφ, a nozzle gap of 42 μm, a syringe ejection pressure of 100 to 400 kPa, and a coating speed of 60 mm / sec. At this time, the ejection pressure is adjusted in such a way that the line width of the curable resin composition becomes about 1.5 mm. Next, tiny droplets of liquid crystal (made by Tokyo Chemical Industry Co., Ltd., "4-pentyl-4-biphenylcarbonitrile") are applied to the entire surface of the frame of the curable resin composition of the substrate coated with the curable resin composition, and another substrate is attached under vacuum. Immediately after lamination, the curable resin composition was irradiated with a metal halide lamp at 100 mW / cm 2 The curable resin composition was pre-cured by irradiating with ultraviolet rays for 30 seconds. Then, the composition was heated at 120° C. for 1 hour for main curing to produce a liquid crystal display element.

[0180] For the obtained liquid crystal display element, the liquid crystal orientation disorder (display unevenness) near the sealant just after the liquid crystal display element is made is confirmed by visual inspection. The orientation disorder is judged according to the color unevenness of the display part, and the situation where the display unevenness is not observed at all in the liquid crystal display element is recorded as "○", and the situation where the display unevenness exists in the peripheral part (within 500um of the curable resin composition) is recorded as "△", and the situation where the display unevenness is not only in the peripheral part, but also extends to the central part above 500um is recorded as "×", and the low liquid crystal contamination is evaluated.

[0181]

Table 1

[0182]

[0183] Industrial Applicability

[0184] According to the present invention, a novel dihydrazide compound can be provided. In addition, the present invention can provide a curable resin composition containing the dihydrazide compound and having excellent storage stability, curability and adhesion, and a sealant for liquid crystal display elements, a vertical conductive material and a liquid crystal display element formed by using the curable resin composition and having excellent low liquid crystal contamination.

Claims

1. A sealant for a liquid crystal display element, characterized in that: The liquid crystal display element sealant is formed by using a curable resin composition containing a curable resin and a thermosetting agent. The thermal curing agent comprises a dihydrazide compound represented by the following formula (1): In formula (1), Ar is a phenyl group or a benzyl group, m is an integer of 0 to 5, and n is an integer of 0 to 5.

2. The sealing agent for liquid crystal display elements according to claim 1, wherein The thermal curing agent comprises a dihydrazide compound represented by the following formula (2): 。 The sealing agent for liquid crystal display elements according to claim 1 or 2, further comprising a photoradical polymerization initiator. 4 . A vertical conductive material comprising the sealing agent for a liquid crystal display element according to claim 1 , 2 or 3 and conductive fine particles. 5 . A liquid crystal display element, comprising the sealing agent for a liquid crystal display element according to claim 1 , 2 or 3 or the vertical conductive material according to claim 4 .

Citation Information

Patent Citations

  • Sealing agent for dropping process of LCD panel

    JP2001133794A

  • Curing resin composition and sealants and end-sealing materials for displays

    WO2002092718A1

  • Stabilised Polyurethanes

    GB1164559A

  • Curable composition, liquid crystal sealing agent and liquid crystal display element

    JP2009230095A

  • Hydrazide compound and curable composition using the same

    JP2019108311A